Work and children in Spain: Challenges and opportunities for equality between men and women - Claudia Hupkau; Jenifer Ruiz-Valenzuela (SERIEs - Journal of the Spanish Economic Association, 2022)
Over the past decades, Spain has seen a striking convergence between women's and men's participation in the labour market. However, this convergence has stalled since the early 2010s. We show that women still fare worse in several important labour market dimensions. Gender inequalities are further aggravated among people with children. Women with children under 16 are much more likely to be unemployed, work part-time or on temporary contracts than men with children of the same age. We show that it is unlikely that preferences alone can account for these gaps. A review of the evidence shows that family policies, such as paternity leave expansions, financial incentives in the form of tax credits for working mothers and subsidised or free childcare for very young children, could help reduce the motherhood penalty. However, such policies are likely to be more effective if combined with advances in breaking up traditional gender roles.
Keywords: J13; J16; J18; 330; Family policy; Gender gaps; Inequality; Motherhood penalty